2018
DOI: 10.1186/s13028-018-0378-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on effects of diet on Lawsonia intracellularis infections in fattening boars in a natural infection model

Abstract: BackgroundLawsonia intracellularis is one of the most economically important pathogens in swine production. This study tested the hypothesis that the composition of diets for pigs has an impact on the excretion of L. intracellularis in a natural infection model.ResultsFifty boars (~ 90 kg BW) from a SPF-farm with a strict hygiene and management regime for reducing the spread of an L. intracellularis infection up to the beginning of the final fattening period were transported, regrouped and randomly allotted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This indicates that lactose was not digested by the fattening pig, rather it was fermented. Furthermore, the increased lactic acid coincided with a reduction in Lawsonia intracellularis, which is a pathogen that can cause intestinal damage and disease in swine [38]. This study, therefore, further demonstrates the potential prebiotic effect from lactose fermentation.…”
Section: Lactose In Growing-finishing Pig Dietssupporting
confidence: 56%
See 1 more Smart Citation
“…This indicates that lactose was not digested by the fattening pig, rather it was fermented. Furthermore, the increased lactic acid coincided with a reduction in Lawsonia intracellularis, which is a pathogen that can cause intestinal damage and disease in swine [38]. This study, therefore, further demonstrates the potential prebiotic effect from lactose fermentation.…”
Section: Lactose In Growing-finishing Pig Dietssupporting
confidence: 56%
“…The adult pig, on the other hand, has limited lactase activity in the small intestine and, therefore, lactose may be a significant substrate for microbial fermentation in the small and large intestine. Pierce et al [38] reported that butyric acid concentration linearly increased and a ratio of acetic acid to propionic acid linearly decreased in the feces of growing-finishing pigs fed diets containing 0 up to 12% lactose. These results indicate that a certain amount of lactose entered the hindgut and was fermented causing shifts in microbial metabolite production.…”
Section: Digestion and Absorption Of Lactose In Suckling And Weanlingmentioning
confidence: 99%
“…The concentrations of these acids were about 140–160 mM (29). Significantly higher concentrations of SCFA could also be measured in fattening boars when fed ad libitum (30). At 218.8 mmol/kg cecal content, the sum of acetate, propionate, and butyrate was considerably higher than in the piglets in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the above study believe that maternal feeding of scFOS may enhance the beneficial microbiota of the sows which are then transmitted to the piglets, where the microbes increase the production of short chain fatty acids in their gut ( 102 ). Another recent study has produced preliminary evidence that feed composition influences L. intracellularis infections in farmed pigs ( 103 ). Though few specific studies have investigated L. intracellularis control by using prebiotics, this approach appears promising and is mediated by the increase in beneficial microbes.…”
Section: Control Of L Intracellularismentioning
confidence: 99%